LBPS 02–31 DEFINITION OF PEDIATRIC HYPERTENSION: ARE BLOOD PRESSURE MEASUREMENTS ON THREE SEPARATE OCCASIONS NECESSARY?. (September 2016) - Sun, Jiahong; Xi, Bo
Abstract : Objective: The 2004 US Fourth Report recommends that diagnosis of pediatric hypertension should be based on blood pressure (BP) measurements on at least three separate occasions. However, there is no sufficient evidence to support this decision. The aim of this systematic review was to assess the change in prevalence of elevated BP obtained on three separate visits in children and adolescents worldwide. Design and Method: Pubmed and Embase databases were searched for eligible studies published in English up to November 15, 2015. Included studies were population-based and reporting about the prevalence of elevated BP in pediatric populations on two or three separate occasions. The decreased percentage of elevated BP between the first and the subsequent one or two visits was calculated to assess the change in prevalence of elevated BP. Results: A total of 22 studies with 179, 561 participants aged 3–20 years were included in the present systematic review. The prevalence of elevated BP decreased across visits, from 4.6%-19.4% at the first visit, to 2.5%-14.2% at the second visit, and to 0.3%-8.2% at the third visit. When compared to visit 1, the prevalence of elevated BP decreased by 10.5%-80.7% at visit 2, and by 48.1%-93.5% at visit 3. Conclusions: The prevalence of elevated BP decreased substantially from the first visit to the subsequent visits. Our results support the recommendation of the 2004 US Fourth Report that repeated measurements at three separate visits might be required to accurately define hypertension in children and adolescents.